The Janus Corner - IE, Cock (Pharmacognosy Communications)
The growing concern in the recent past over toxic effects of various synthetic drugs has forced the researchers, academicians and doctors to consider some steps for preventing the misuse of such drugs. The occurrence of side effects after a long term use of synthetic drugs always feared during treatment of chronic diseases. Such a possibility is experienced to be of negligible extent in the case of herbal drugs and other medicines obtained from natural sources. These are some reasons which the authorities in this field to reconsider the use of herbal medicines and to give enough attention to the development of sciences of phytopharmaceuticals. The development of science of phytopharmaceuticals and the hopes for remedies in chronic diseases has generated new enthusiam in researches workers to develop herbal medicines.[1] Phytopharmaceuticals the rage and age of today are in considerable demand. Pharmacognosy can now be righty be called as “Science of phytopharmaceuticals” in today’s era.[2]